2021
DOI: 10.1111/jocs.16066
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term laryngotracheal complications following cardiac surgery

Abstract: Background and aim of the study: Long-term laryngotracheal complications have not been described in adult patients undergoing cardiac surgery. The purpose of this study was to determine the incidence of and risk factors for laryngotracheal complications following cardiac surgery.Methods: A retrospective chart review of patients at high risk for laryngotracheal complications following cardiac surgery between 2006 and 2016 was performed.High-risk patients were reviewed to determine the presence of laryngotrachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…The role of surgery in the development of SGS is not well known. Three studies have found an association between SGS and cardiac surgery [12][13][14]. However, no studies or case reports discuss the development of SGS after endoscopic skull base surgery or other otolaryngologic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The role of surgery in the development of SGS is not well known. Three studies have found an association between SGS and cardiac surgery [12][13][14]. However, no studies or case reports discuss the development of SGS after endoscopic skull base surgery or other otolaryngologic surgeries.…”
Section: Discussionmentioning
confidence: 99%